How Persistent Is Generalised Trust? - Dawson, Chris (Sociology, 2019)
There are at least two competing views on the foundations of generalised trust: experiential and cultural. The experiential perspective emphasises that trust is fragile and remains open to environmental influences throughout life, whilst the cultural perspective asserts that trust is a stable trait established early in pre-adult life through intergenerational transmission mechanisms. Utilising an innovative methodology applied to a major UK longitudinal survey, this article tests these alternative accounts by analysing the persistence of generalised trust throughout the life-course. In support of the cultural perspective, trust is found to be a relatively stable, persistent human trait. Whilst generalised trust is open to change, these changes are however temporary with an overriding tendency for individuals to revert back to their initial, long-term level. Greater emphasis should be placed on the establishment of initial, pre-adult trust, as changes induced by post-childhood environmental forces are likely to be prone to rapid decay.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8wMDM4MDM4NTE3NzE4OTkx